Study of Behaviour Swelling Potential of Expansive Soil on Swelling Test With Cycles of Loading and Unloading - Andi, Hasyim Dhafirozi; Rahayu, Wiwik (ASTONJADRO, 2025)
Expansive soil has the characteristic to swell and shrink that are capable to cause crack on the highways surface. The swell and shrink behaviour of expansive soil are influenced by several factors, one of those is surcharge. Surcharge in highways road are traffic loads. To determine the form of behaviour caused by surcharge on expansive soil, the number of loading and unloading were performed on the oedometer test with the swelling pressure as the maximum stress of each cycles. The purpose of this study to investigate the behaviour of swelling potential of expansive soil of each cycles. The results shown that the sample with lowest moisture content exhibited the largest swelling in primary phase and the lowest in secondary phase. The initial swelling potential presented that sample with lowest moisture content did not always swell larger than the sample with higher moisture content. As the number of loading and unloading cycles increased, the swelling potential of all the samples performed similar behaviour. The most significant change of swelling potential occurred from zero to first cycle. After first cycle, the difference of swelling potential tended to similar. This indicated that all the samples tended to reach the stable conditions. The most influence factors that caused swelling potential decreased with increasing number of cycles were the threshold stress and the swelling pressure. The threshold stress caused expansive soil experienced irreversible deformation. While the swelling pressure caused larger swelling in the beginning of the unloading phase due to repulsive force.